Novel duplication of the cell adhesion molecule L1-like gene in an individual with cognitive impairment, tall stature, and obesity: A case report - Onate-Quiroz, Kenny V.; Nwosu, Benjamin Udoka; Salemi, Parissa (Frontiers in Neurology, 2023)
The gene that codes for the close homolog of L1 (CHL1 gene) is located in the 3p26.3 cytogenetic band in the distal portion of the 3p chromosome. This gene is highly expressed in the central nervous system and plays an important role in brain formation and plasticity. Complete or partial CHL 1 gene-deficient mice have demonstrated neurocognitive deficits. In humans, mutations of the CHL 1 gene are infrequent with most mutations described in the literature as deletions. This case report describes an individual with a duplication in the CHL 1 and a presentation consistent with a syndromic form of neurocognitive impairment. To the best of our knowledge, this mutation has not been previously described in the literature.